Low-temperature features of thermodynamics of an open isotropic Heisenberg chain - Zvyagin, A.A.; Makarova, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Low-temperature magnetic susceptibility and specific heat of an antiferromagnetic Heisenberg chain with open boundary conditions are calculated with the help of exact Bethe ansatz method. These characteristics behave with temperature in a different way from the ones of a periodic chain.